Experiences of Outpatient Clinics and Opinions of Telehealth by Caucasian and South Asian Patients' With Celiac Disease. (17th May 2021) - Muhammad, Humayun; Reeves, Sue; Ishaq, Sauid; Jeanes, Yvonne
Outpatient clinics are an important part of chronic disease management, including that of celiac disease. During the coronavirus disease 2019 (COVID-19) global pandemic, telephone and online video consultations with health care professionals have substantially increased. This study aimed to explore the experience and opinions of adults, with celiac disease, toward face-to-face clinic appointments and alternatives, such as telehealth. Semistructured qualitative interviews with 37 patients were undertaken (75% White Caucasians, 25% South Asians; 29 patients were not adhering to the gluten-free diet). Interviews were recorded, transcribed, and analyzed by NVivo. Frequently reported issues with face-to-face appointments included travel and car parking costs, needing to take time off work, and frequent changes to appointment time. In addition, South Asian patients highlighted issues with linguistics barriers. Telephone consultations were considered acceptable and practical by the majority of patients based on ease and convenience. Online video consultations were favored by just 9 patients, however it is acknowledged that since the COVID-19 pandemic, there has been a greater exposure to this type of technology. These patient experiences can inform health care service development and are not biased by external health concerns connected with in-person visits during the pandemic.